Nuevas aportaciones para la historia de la evolución tecnológica en el Bajo Imperio - Alfaro Giner, Carmen (Antigüedad y Cristianismo, 1991)
In her study the author enters into the controversial subject of the origins of the mechanical horizontal loom in the Late Empire. The posible and gradual substitution process of traditional textile techniques must have brought about a series of important labour changes, and caused serious economical and social effects.